Workshop Manajemen Kesehatan dan Keselamatan Kerja Dalam Situasi Pandemi Bagi Perekam Medis RS Rujukan COVID-19 Kota Semarang - Tiara Fani; Kriswiharsi Kun Saptorini; Retno Astuti Setijaningsih; Tuplikhatun Tuplikhatun; Tasya Aulia Trengga Dewi (LPPM UNIVERSITAS DIAN NUSWANTORO, 2022)
During the COVID-19 outbreak, medical record staff also have a risk of COVID-19. The Medical Record Department should consider the occupational health and safety implementation during the pandemic to protect their staff. This activity aimed to increase the knowledge of Medical Record officers in Semarang City about the risk of disease exposure inside or outside their work area. This activity was held in a workshop through: a discussion of the topic needs with related groups, pre-test, topic presentation, and post-test. Participants in this activity were 17 medical recorders from several COVID-19 referral hospitals in Semarang City. The results of this workshop showed that the participants' knowledge of occupational health and safety management and strategies for supporting medical record services in a pandemic situation in most of the participants (83.3%) increased. Knowledge of ideal hand washing time to prevent disease needs more consideration by providing information media at handwashing stations or in several areas as a reminder for officers to provide better practice on their health and work safety protocols.